2003
DOI: 10.1046/j.1469-8137.2003.00734.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Swedish isolates of Phytophthora quercina to Quercus robur in two different soils

Abstract: Summary• Several studies have demonstrated the involvement of soil-borne Phytophthora species, especially Phytophthora quercina , in European oak decline. However, knowledge about the pathogenicity of P. quercina in natural forest soils is limited.• The short-term effects of two south-Swedish isolates of P. quercina on root vitality of Quercus robur seedlings grown in two different soils, one high pH, nutrient-rich peat-sand mixture and one acid, nitrogen-rich but otherwise nutrient-poor forest soil are descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 31 publications
6
46
1
2
Order By: Relevance
“…P. cinnamomi (widely distributed, with likely origin of Papua New Guinea) is a worldwide invasive pest, one of the most destructive root pathogens, and cold temperatures are thought to limit its distribution (Brasier, 1996). Phytophthora diseases are most prevalent in relatively alkaline, clay-rich soils Jönsson et al, 2005); recent evidence indicates that, contrary to earlier belief, they can also infect roots in acidic soils (Jönsson et al, 2003;Jönsson, 2004). Phytophthora diseases can infect fine roots during periods of excess or limited soil moisture, and may be particularly successful when conditions rapidly change from one moisture extreme to the other (Brasier, 1996;Jung et al, 2003;Jönsson, 2006).…”
Section: Emergent Biotic Agents Involved In Oak Decline: Pathogensmentioning
confidence: 99%
“…P. cinnamomi (widely distributed, with likely origin of Papua New Guinea) is a worldwide invasive pest, one of the most destructive root pathogens, and cold temperatures are thought to limit its distribution (Brasier, 1996). Phytophthora diseases are most prevalent in relatively alkaline, clay-rich soils Jönsson et al, 2005); recent evidence indicates that, contrary to earlier belief, they can also infect roots in acidic soils (Jönsson et al, 2003;Jönsson, 2004). Phytophthora diseases can infect fine roots during periods of excess or limited soil moisture, and may be particularly successful when conditions rapidly change from one moisture extreme to the other (Brasier, 1996;Jung et al, 2003;Jönsson, 2006).…”
Section: Emergent Biotic Agents Involved In Oak Decline: Pathogensmentioning
confidence: 99%
“…The most frequently recovered species was P. quercina. Phytophthora quercina was found to cause root infection in oak seedlings, in artificial soil mixtures as well as in acid forest soils, with subsequent necrosis and die-back of the root systems [21,22]. A weak association was also found between the occurrence of P. quercina and the vitality of mature oak stands [23].…”
Section: Introductionmentioning
confidence: 98%
“…In our experiment, it was demonstrated that P. quercina can infect not only fine roots (Jung et al 1999;Jönsson et al 2003) but also tissues of Turkey oak stems. Also, most of the investigated isolates show the ability to grow in the living tissues without causing any visible disease symptoms.…”
Section: Discussionmentioning
confidence: 52%
“…The pathogenicity of south-Swedish isolates of P. quercina in acid forest soils under restricted water availability was studied by Jönsson et al (2003). They found that in the acid forest soil, the percentage of fineroot dieback was high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation